Handbook for integrated soil fertility management - Fairhurst, Thomas (CTA / CABI, 2012)
This handbook presents Integrated Soil Fertility Management, commonly known as ISFM, as a key contributor to improving Africa’s soil and crop productivity, especially for the key staples in the continent that include maize, legumes, rice, cassava, bananas, sorghum, millet and coffee. It is meant for training of extension workers on soil fertility management techniques in sub-Saharan Africa and for workers involved in rural development that would like to learn more about the principles of ISFM. The handbook is also a useful primer on ISFM for educational organizations such as universities and technical colleges, and organizations involved in the development of policy on agriculture and rural development that need reference materials on ISFM techniques.